A high entropy ceramic thermal barrier coating and preparation method thereof

Through the plasma spraying physical vapor deposition technology of (Y0.2Sm0.2Eu0.2Gd0.2Yb0.2)2Zr2O7 high-entropy ceramic material, a feather-type columnar thermal barrier coating with excellent high-temperature phase stability and mechanical properties was prepared, and the current solution was solved. There are problems such as insufficient phase stability and low strain tolerance at high temperatures, and are suitable for high-temperature hot end components.

CN116377372BActive Publication Date: 2024-12-13GUANGDONG INST OF NEW MATERIALS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310332788.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2024-12-13
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The existing high-temperature thermal barrier coatings have insufficient phase stability, low strain tolerance and poor mechanical properties of above 1200°C.

Method used

Using (Y0.2Sm0.2Eu0.2Gd0.2Yb0.2)2Zr2O7 high-entropy ceramic material, a thermal barrier coating with feather-shaped columnar high-strain tolerance structure is prepared by plasma spraying physical vapor deposition technology (PS-PVD), using rare earth elements The high entropy transformation improves the high-temperature phase stability and mechanical properties of the material.

Benefits of technology

Excellent high-temperature phase stability and good mechanical properties below 1600°C are achieved, and the problem of insufficient fracture toughness of traditional ceramic coatings is overcome. It is suitable for high-temperature thermal barrier coating applications of aircraft engines and gas turbines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116377372B_ABST
    Figure CN116377372B_ABST
Patent Text Reader

Abstract

The invention discloses a high entropy ceramic thermal barrier coating and a preparation method thereof. The chemical formula of the high entropy ceramic thermal barrier coating is (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7, where the percentage of the molar number of each rare earth element to the total molar number of all rare earth elements is 18% to 22% respectively. The elements in this high entropy ceramic thermal barrier coating are evenly distributed on the coating without element segregation, and have a fluorite phase structure. The cross-sectional morphology is a feather-shaped columnar high strain tolerance structure: the bottom coating is composed of columnar main crystals and dendrite sequences, with a large porosity; the top is composed of a loose sequence of columnar crystals, and many ungrown secondary dendrites constitute the "cauliflower head" area. This coating material has both excellent high-temperature phase stability and good mechanical properties, which is of great significance to the development and application of advanced structure ultra-high temperature thermal barrier coating technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal barrier coating materials and preparation methods, and in particular to a high entropy ceramic thermal barrier coating and a preparation method thereof. Background Art

[0002] Thermal barrier coatings achieve thermal protection by preparing high-temperature resistant ceramic materials on the surface of the substrate. Preparing thermal barrier coatings with high bonding strength, excellent thermal insulation performance, and stable high-temperature service performance on the surface of the blade is one of the key technologies to improve the performance of engine blades. Yttria-stabilized zirconia (YSZ) has the advantages of high thermal expansion coefficient, high fracture toughness, and high thermal shock resistance, but its phase stability and sintering resistance are insufficient above 1200°C; single-component rare earth zirconate (RE2Zr2O7) has lower thermal conductivity, higher phase stability and high-temperature corrosion resistance than YSZ, but its toughness and thermal expansion coefficient are poor. With the rapid development of aviation engine and gas turbine technology, the gas inlet temperature continues to increase. In order to meet the demand for higher service temperatures for gas turbine engine blades, it is urgent to develop new high-phase stability ultra-high temperature thermal barrier coating ceramic layer materials.

[0003] In 2015, Rost et al. synthesized a five-component entropy-stabilized oxide (MgCoNiCuZn)O using MgO, CoO, NiO, CuO and ZnO as raw materials, which showed a stable single-phase rock salt structure and good application prospects. Since then, the concept of "high entropy" has been gradually applied to the field of ceramics. By dissolving 5 or more ceramic principal components in an equimolar ratio or a nearly equimolar ratio to form a high-entropy ceramic with a certain structure, this multi-principal component solid solution has a high configurational entropy. Under the action of four core effects (high entropy effect, hysteresis diffusion effect, lattice distortion effect, and cocktail effect), it usually exhibits good high-temperature phase stability, high thermal expansion coefficient, low thermal conductivity, good thermal shock resistance, CMAS resistance and other excellent properties. The method of converting existing material systems into high entropy provides a new way to design high-performance thermal barrier coating materials. Zhang Guojun's team used atmospheric plasma spraying technology (APS) to prepare (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )2Zr2O7 high entropy rare earth zirconate thermal barrier coating, the thermal cycle life is better than La2Zr2O7, and the thermal cycle before and after are fluorite phase structure; Zhao Xiaofeng's team based on the ZYTO system, respectively, using atmospheric plasma spraying (APS) and electron beam physical vapor deposition (EB-PVD) technology to prepare multi-component high entropy oxide Zr 1-4x Y x Ta x Nb x Yb xO2 ultra-high temperature thermal barrier coating can maintain the tetragonal phase at a high temperature of 1600℃. At present, the research on high entropy ceramic thermal barrier coatings is mainly focused on bulk materials, and the preparation and characterization of coatings are relatively rare; plasma spray physical vapor deposition technology (PS-PVD) as a new preparation technology combines the advantages of APS and EB-PVD technologies, and can prepare thermal barrier coatings with feather-shaped columnar high strain tolerance structures, which have both low thermal conductivity and high thermal shock resistance. It is expected to overcome the intrinsic material defects of low fracture toughness of traditional ceramic coatings through advanced structural preparation technology. However, there are no reports on high entropy ceramic thermal barrier coatings prepared by PS-PVD technology.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a high entropy ceramic thermal barrier coating and a preparation method thereof, so as to improve the problems of insufficient high temperature phase stability, low strain tolerance and poor mechanical properties existing in the thermal barrier coating prepared by the conventional thermal spraying process of the existing material system.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a high entropy ceramic thermal barrier coating, the chemical formula of which is (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7, wherein the percentage of the molar number of each rare earth element to the total molar number of all rare earth elements is 18% to 22% respectively.

[0008] In some embodiments, the high entropy ceramic thermal barrier coating has a thickness of 350-400 μm.

[0009] The above-mentioned high-entropy ceramic thermal barrier coating has a fluorite phase structure, and its cross-sectional morphology is a feather-shaped columnar high strain tolerance structure: the bottom coating is composed of columnar primary crystals and dendrite sequences, with a large porosity; the top is composed of a loose sequence of columnar crystals, and numerous ungrown secondary dendrites constitute the "cauliflower head" area.

[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned high entropy ceramic thermal barrier coating, comprising: weighing raw materials and subjecting them to wet ball milling, mixing, and drying, and crushing and secondary granulating the obtained mixed powder after pre-sintering to obtain (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 agglomerated powder, and then (Y 0.2 Sm0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 agglomerated powder is deposited on the surface of the substrate to form (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating.

[0011] In some embodiments, the raw materials include ZrO2 and rare earth oxide powders, and the rare earth oxides include Y2O3, Sm2O3, Eu2O3, Gd2O3 and Yb2O3.

[0012] In some embodiments, the particle size of ZrO2 is 0.2-1 μm, and the mass purity is ≥99.99%.

[0013] In some embodiments, the particle size of the rare earth oxide is 5-10 μm, and the mass purity is ≥ 99.99%.

[0014] In some embodiments, the ball milling medium of wet ball milling is ethanol, the ball milling beads are made of ZrO2, the rotation speed is 300-400 rpm, and the ball milling mixing time is 8-24 hours.

[0015] In some embodiments, the drying temperature is 105-120° C., and the drying time is 10-12 h.

[0016] In some embodiments, the pre-sintering temperature is 1500-1600° C., and the pre-sintering time is 2-10 h.

[0017] In some embodiments, the spray drying parameters in the secondary granulation process are: solid content 40-65%, dispersant 6-10% PAA, binder 8-10% PVP, inlet temperature 240-260°C, outlet temperature 110-130°C, feed speed 30-50rpm, spray speed 5-6m 3 / h, air pressure 2-3bar.

[0018] In some embodiments, (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2When the Zr2O7 agglomerated powder is deposited on the substrate surface, the spraying parameters are: spraying distance 800-1000mm, spray gun moving speed 300-500mm / s, temperature 900-1000℃, powder feeding rate 5-10g / min, carrier gas flow 5-20SLPM, argon flow 25-40SLPM, helium flow 40-60SLPM, oxygen flow 0-5SLPM, current 2400-2700A, cabin pressure 4-6×10 -5 MPa.

[0019] In a third aspect, the present invention also provides the application of the above-mentioned high entropy ceramic thermal barrier coating in aircraft engines and gas turbines.

[0020] The present invention has the following beneficial effects:

[0021] The present invention utilizes the cocktail effect among the four core effects of high entropy ceramics, selects rare earth metal elements with good plasticity and ductility to carry out high entropy transformation on the GZO system, and obtains (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating. The elements in this high entropy ceramic thermal barrier coating are evenly distributed on the coating without element segregation, and it has a fluorite phase structure. The cross-sectional morphology is a feather-shaped columnar high strain tolerance structure: the bottom coating is composed of columnar main crystals and dendrite sequences, with a large porosity; the top is composed of a loose sequence of columnar crystals, and many ungrown secondary dendrites constitute the "cauliflower head" area. This high entropy ceramic thermal barrier coating has both excellent high-temperature phase stability and good mechanical properties. The non-line-of-sight characteristic deposition process used is conducive to the preparation of coatings on the special-shaped structural surfaces and shielded areas of hot end components, which is of great significance to the development of advanced structure ultra-high temperature thermal barrier coating technology and its application in aircraft engines and gas turbines. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 (Y prepared in Example 1 and Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) XRD pattern comparison of 2Zr2O7 pre-sintered powder;

[0024] Figure 2 (Y prepared in Example 1 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) SEM image of 2Zr2O7 pre-sintered powder after crushing;

[0025] Figure 3 (Y prepared in Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) SEM image of 2Zr2O7 pre-sintered powder after crushing;

[0026] Figure 4 (Y prepared in Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )SEM image of the surface of 2Zr2O7 high entropy ceramic thermal barrier coating;

[0027] Figure 5 (Y prepared in Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) SEM and EDS comparison of the cross section of 2Zr2O7 high entropy ceramic thermal barrier coating;

[0028] Figure 6 (Y prepared in Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) XRD comparison diagram of 2Zr2O7 pre-sintered powder before and after high temperature heat treatment at 1600℃ for 10h;

[0029] Figure 7 This is the XRD comparison diagram of commercially available YSZ powder before and after high-temperature heat treatment at 1600℃ for 10h. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0031] At present, most high-entropy ceramic powders are synthesized by solid-phase reaction method. The powders usually obtained cannot meet the powder feeding requirements of spraying equipment due to problems such as poor sphericity and uneven particle size distribution. At the same time, high-entropy ceramics have low fracture toughness, and the prepared coatings are extremely prone to peeling during the cooling process, which eventually leads to failure. Therefore, most of the preparation and characterization of high-entropy ceramics are mainly achieved through bulk materials, which cannot represent the performance of high-entropy ceramic coatings. In order to provide a high-entropy ceramic thermal barrier coating, the inventors of the present invention designed a composition of (Y2Zr2O7, GZO) based on the gadolinium zirconate (Gd2Zr2O7, GZO) system through a high-entropy method. 0.2 Sm 0.2 E u0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic rare earth zirconate, and the coating was prepared using PS-PVD technology.

[0032] The high entropy ceramic thermal barrier coating and its preparation method provided by the present invention are described in detail below.

[0033] The present invention provides a high entropy ceramic thermal barrier coating, the chemical formula of which is (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7, wherein the percentage of the molar number of each rare earth element to the total molar number of all rare earth elements is 18% to 22%. The high entropy ceramic thermal barrier coating of the present invention is a multi-component single-phase solid solution formed by solid solution of Y2O3, ZrO2, Sm2O3, Eu2O3, Gd2O3 and Yb2O3.

[0034] In the present invention, the thickness of the high entropy ceramic thermal barrier coating prepared by the PS-PVD technology is 350-400 μm.

[0035] Specifically, the thickness of the high entropy ceramic thermal barrier coating may be 350 μm, 360 μm, 370 μm, 380 μm, 390 μm or 400 μm, or any other value within the range of 350-400 μm.

[0036] Through testing, it was found that the high entropy ceramic thermal barrier coating of the present invention has a fluorite phase structure, and the cross-sectional morphology of the coating is a feather-shaped columnar high strain tolerance structure: the bottom coating is composed of columnar main crystals and dendrites, with a large porosity; the top is composed of a loose sequence of columnar crystals, and many ungrown secondary dendrites constitute the "cauliflower head" area. The elements are evenly distributed on the coating, and there is no element segregation. The coating has good mechanical properties (low elastic modulus and hardness). At the same time, the high entropy ceramic material has excellent high-temperature phase stability at 1600°C.

[0037] In order to prepare the above-mentioned high entropy ceramic thermal barrier coating, the inventors of the present invention firstly used PS-PVD technology to prepare the high entropy ceramic thermal barrier coating, which includes the following steps:

[0038] (1) According to (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )Zr2O7 (i.e., the molar ratio is 1:1:1:1:1:5) and ZrO2 and rare earth oxides Y2O3, Sm2O3, Eu2O3, Gd2O3 and Yb2O3 are weighed as raw materials.

[0039] In the present invention, the particle size of ZrO2 powder in the above raw materials is 0.2-1μm, and the mass purity is ≥99.99%; the particle size of the powders of rare earth oxides Y2O3, Sm2O3, Eu2O3, Gd2O3 and Yb2O3 is 5-10μm, and the mass purity is ≥99.99%.

[0040] Specifically, the particle size of the ZrO2 powder can be 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or 1μm, or any other value within the range of 0.2-1μm.

[0041] Specifically, the particle size of the rare earth oxide powder may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, or any other value within the range of 5-10 μm.

[0042] Within the above-mentioned particle size range, it is possible to ensure sufficient melting under the conditions of plasma spray physical vapor deposition to obtain good coating quality; in addition, the above-mentioned particle size range can also avoid the problem of easy gun clogging caused by too small particle size.

[0043] (2) The raw materials, ball milling media and ball milling beads are placed in a polyurethane ball milling tank for wet ball milling. The resulting mixed slurry is placed in a forced air drying oven and dried to obtain a mixed powder.

[0044] In the present invention, the ball milling medium is ethanol; the material of the ball milling beads is ZrO2.

[0045] In the present invention, the rotation speed of the wet ball milling is 300-400 rpm, and the ball milling mixing time is 8-24 hours.

[0046] Specifically, the rotation speed of the wet ball milling can be 300 rpm, 320 rpm, 350 rpm, 380 rpm or 400 rpm, or any other value within the range of 300-400 rpm. The ball milling mixing time can be 8 h, 10 h, 12 h, 15 h, 18 h or 24 h, or any other value within the range of 8-24 h.

[0047] In the present invention, the drying temperature is 105-120° C. and the drying time is 10-12 hours.

[0048] Specifically, the drying temperature may be 105° C., 110° C., 115° C. or 120° C., or any other value within the range of 105-120° C. The drying time may be 10 h, 11 h or 12 h, or any other value within the range of 10-12 h, until the drying is completed.

[0049] (3) Pre-sintering the mixed powder at 1500-1600° C. for 2-10 hours to obtain pre-sintered powder.

[0050] Specifically, the pre-sintering temperature may be 1500° C., 1520° C., 1550° C., 1580° C. or 1600° C., or any other value within the range of 1500-1600° C. The pre-sintering time may be 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, or any other value within the range of 2-10 h.

[0051] (4) The pre-sintered powder is subjected to a series of pulverization processes and then subjected to secondary granulation by a spray dryer to obtain (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 agglomerated powder.

[0052] In the present invention, the parameters of spray drying are: solid content 40-65%, dispersant PAA 6-10%, binder PVP 8-10%, inlet temperature 240-260°C, outlet temperature 110-130°C, feed speed 30-50rpm, spray speed 5-6m 3 / h, air pressure 2-3bar.

[0053] Specifically, the solid content may be 40%, 45%, 50%, 55%, 60% or 65%, or any other value within the range of 40-65%.

[0054] Specifically, the content of the dispersant PAA can be 6%, 7%, 8%, 9% or 10%, or any other value within the range of 6-10%. The content of the binder PVP can be 8%, 8.5%, 9%, 9.5% or 10%, or any other value within the range of 8-10%.

[0055] Specifically, the inlet temperature may be 240° C., 245° C., 250° C., 255° C. or 260° C., or any other value within the range of 240-260° C. The outlet temperature may be 110° C., 115° C., 120° C., 1250° C. or 130° C., or any other value within the range of 110-130° C.

[0056] Specifically, the feed rotation speed may be 30 rpm, 35 rpm, 40 rpm, 45 rpm or 50 rpm, or any other value within the range of 30-50 rpm.

[0057] Specifically, the spray speed can be 5m 3 / h、5.2m 3 / h、5.5m 3 / h、5.8m 3 / h or 6m 3 / h, or 5-6m 3 Any other value within the range of / h.

[0058] Specifically, the air pressure may be 2 bar, 2.2 bar, 2.5 bar, 2.8 bar or 3 bar, or any other value within the range of 2-3 bar.

[0059] Under the above spray drying parameter conditions, the agglomerated powder obtained by secondary granulation has the characteristics of high sphericity and good fluidity.

[0060] (5) Cut the high temperature alloy round rod into The disc-shaped specimens or the hot end parts of aircraft engines and gas turbines were used as the substrate, and ultrasonic cleaning was performed using kerosene, acetone and ethanol respectively. The surface was sandblasted with 280# corundum white sand. After the residual sand was blown away by compressed air, ethanol was brushed again for cleaning. The agglomerated powder was deposited on the substrate surface using PS-PVD technology to form (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating.

[0061] In the present invention, (Y 0.2 Sm 0.2 Eu 0.2 G0.2 Yb 0.2 When the Zr2O7 agglomerated powder is deposited on the substrate surface, the spraying parameters are: spraying distance 800-1000mm, spray gun moving speed 300-500mm / s, temperature 900-1000℃, powder feeding rate 5-10g / min, carrier gas flow rate 5-20SLPM, argon flow rate 25-40SLPM, helium flow rate 40-60SLPM, oxygen flow rate 0-5SLPM, current 2400-2700A, cabin pressure 4-6×10 -5 MPa.

[0062] Specifically, the spraying distance may be 800 mm, 850 mm, 900 mm, 950 mm or 1000 mm, etc., or any other value within the range of 800-1000 mm.

[0063] Specifically, the movement speed of the spray gun can be 300 mm / s, 350 mm / s, 400 mm / s, 450 mm / s, or 500 mm / s, or any other value within the range of 300-500 mm / s.

[0064] Specifically, the spraying temperature may be 900°C, 920°C, 950°C, 980°C or 1000°C, or any other value within the range of 900-1000°C.

[0065] Specifically, the powder feeding rate may be 5 g / min, 6 g / min, 7 g / min, 8 g / min, 9 g / min, or 10 g / min, or any other value within the range of 5-10 g / min.

[0066] Specifically, the carrier gas flow rate may be 5 SLPM, 8 SLPM, 10 SLPM, 12 SLPM, 15 SLPM or 20 SLPM, or any other value within the range of 5-20 SLPM.

[0067] Specifically, the argon gas flow rate may be 25 SLPM, 30 SLPM, 32 SLPM, 35 SLPM, 38 SLPM or 40 SLPM, or any other value within the range of 25-40 SLPM.

[0068] The helium flow rate may be 40 SLPM, 45 SLPM, 50 SLPM, 55 SLPM or 60 SLPM, or any other value within the range of 40-60 SLPM.

[0069] The oxygen flow rate can be 0SLPM, 1SLPM, 2SLPM, 3SLPM, 4SLPM or 5SLPM, or any other value within the range of 0-5SLPM.

[0070] The current may be 2400A, 2500A, 2600A or 2700A, or any other value within the range of 2400-2700A.

[0071] The cabin pressure can be 4×10 -5 MPa, 4.5×10 -5 MPa, 5×10 -5 MPa, 5.5×10 -5 MPa or 6×10 -5 MPa, or 4-6×10 -5 Any other value within the range of MPa.

[0072] At present, due to the low fracture toughness of high entropy ceramics, the prepared coating is extremely easy to peel off during the cooling process, which eventually leads to failure, so high entropy ceramic coatings cannot be prepared. In order to overcome this problem, the present invention prepares a high entropy ceramic coating. The inventors first use PS-PVD technology to prepare (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating, this technology combines the advantages of APS and EB-PVD technology, and by controlling the spraying parameters, it can prepare high entropy ceramic thermal barrier coatings with good thermal and mechanical properties. In addition, this technology has non-line-of-sight deposition characteristics, which is more conducive to the preparation of thermal barrier coatings on the surfaces of special structures and shielded areas of hot end components compared to traditional APS and EB-PVD technologies, which is of great significance for the application of high entropy ceramic thermal barrier coatings in aircraft engines and gas turbines.

[0073] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0074] Example 1

[0075] This embodiment provides a method for preparing a high entropy ceramic thermal barrier coating, and the specific steps are as follows:

[0076] S1. Weigh the original powders of Y2O3, Sm2O3, Eu2O3, Gd2O3, Yb2O3 (particle size 5-10 μm, purity 99.99 wt.%) and ZrO2 powder (particle size 0.2-1 μm, purity 99.99 wt.%) in a molar ratio of 1:1:1:1:1:5 (the molar ratio of rare earth elements is 0.2:0.2:0.2:0.2:0.2:1);

[0077] S2. Using ethanol as the medium and ZrO2 balls as the ball milling beads, the mixture was milled at 300 rpm on a planetary ball mill for 10 h to obtain a mixed slurry, and the slurry was placed in a blast drying oven at 110 ° C for 12 h until it was completely dried to obtain a mixed powder;

[0078] S3. The mixed powder is loaded into an alumina crucible, and then placed in a muffle furnace, and kept at 1600-1650°C for 2h to obtain a pre-sintered powder; the pre-sintered powder is ground, crushed, and ball-milled for 2-4h, and a suspension is prepared according to 40% solid content of the powder, 6% PAA solution and 10% PVP solution, and secondary granulation is performed by a spray dryer to obtain agglomerated powder with high sphericity and good fluidity;

[0079] S4. Cut high temperature alloy round bars into The disc-shaped specimens or the hot end parts of aircraft engines and gas turbines are used as the substrate. The substrate is first ultrasonically cleaned in kerosene for 10 minutes, then ultrasonically cleaned in acetone and ethanol for 10 minutes respectively, and the surface is sandblasted with 280 corundum white sand. After the residual sand is blown away by compressed air, it is brushed with ethanol for cleaning again. The agglomerated powder is deposited on the surface of the substrate using PS-PVD technology to form (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating.

[0080] Among them, (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 The spraying parameters of 2Zr2O7 coating are as follows: spraying distance 800-1000mm, preheating gun speed 300-400mm / s, spraying gun speed 400-500mm / s, temperature 900-1000℃, powder feeding rate 5-10g / min, carrier gas flow 5-20SLPM, argon flow 25-40SLPM, helium flow 40-60SLPM, oxygen flow 0-5SLPM, current 2400-2700A, cabin pressure 5-10×10 -5 MPa.

[0081] The obtained (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )The thickness of the 2Zr2O7 coating is 346μm.

[0082] Figure 2 The (Y0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 pre-sintered powder after crushing. It can be seen from the figure that after grinding, crushing and ball milling for 2-4 hours, the particle size of the pre-sintered powder has reached the micron level, and the particle size distribution is relatively uniform, but there are still a small number of large-sized particles with a particle size of more than 10μm, which may affect the particle size and sphericity of the agglomerated powder after granulation.

[0083] Example 2

[0084] This embodiment provides a method for preparing a high entropy ceramic thermal barrier coating, and the specific steps are as follows:

[0085] S1. Weigh the original powders of Y2O3, Sm2O3, Eu2O3, Gd2O3, Yb2O3 (particle size 5-10 μm, purity 99.99 wt.%) and ZrO2 powder (particle size 0.2-1 μm, purity 99.99 wt.%) in a molar ratio of 1:1:1:1:1:5 (the molar ratio of rare earth elements is 0.2:0.2:0.2:0.2:0.2:1);

[0086] S2. Using ethanol as the medium and ZrO2 balls as the ball milling beads, the mixture was milled at 300 rpm on a planetary ball mill for 10 h to obtain a mixed slurry, and the slurry was placed in a blast drying oven at 110 ° C for 12 h until it was completely dried to obtain a mixed powder;

[0087] S3. The mixed powder is loaded into an alumina crucible, and then placed in a muffle furnace, and kept at 1550°C for 6 hours to obtain a pre-sintered powder; the pre-sintered powder is ground, crushed, and ball-milled for 10 hours, and a suspension is prepared according to 40% solid content of the powder, 6% PAA solution and 10% PVP solution, and secondary granulation is performed by a spray dryer to obtain agglomerated powder with high sphericity and good fluidity;

[0088] S4. Cut high temperature alloy round bars into The disc-shaped specimens or the hot end parts of aircraft engines and gas turbines are used as the substrate. The substrate is first ultrasonically cleaned in kerosene for 10 minutes, then ultrasonically cleaned in acetone and ethanol for 10 minutes respectively, and the surface is sandblasted with 280 corundum white sand. After the residual sand is blown away by compressed air, it is brushed with ethanol for cleaning again. The agglomerated powder is deposited on the surface of the substrate using PS-PVD technology to form (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating.

[0089] Among them, (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 The spraying parameters of 2Zr2O7 coating are as follows: spraying distance 800-1000mm, preheating gun speed 300-400mm / s, spraying gun speed 400-500mm / s, temperature 900-1000℃, powder feeding rate 5-10g / min, carrier gas flow 5-20SLPM, argon flow 25-40SLPM, helium flow 40-60SLPM, oxygen flow 0-5SLPM, current 2400-2700A, cabin pressure 5-10×10 -5 MPa.

[0090] The obtained (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )The thickness of the 2Zr2O7 coating is 360μm.

[0091] Figure 1 (Y prepared in Example 1 and Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) XRD spectrum comparison of 2Zr2O7 pre-sintered powder. It can be seen that the pre-sintered powders prepared in the two embodiments both present a single-phase defective fluorite structure without the generation of impurities or second phases.

[0092] Figure 3 (Y prepared in Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 pre-sintered powder after crushing. It can be seen that after 2-4 hours of grinding, crushing and ball milling, the large-sized particles in the pre-sintered powder have disappeared. Compared with Example 1, the particle size of the pre-sintered powder after crushing in Example 2 is smaller and the particle size distribution is more uniform.

[0093] Figure 4 (Y prepared in Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2)SEM image of the surface of 2Zr2O7 high entropy ceramic thermal barrier coating. It can be seen that the surface morphology of the coating is a "cauliflower head" structure, and the size and distribution of the "cauliflower head" are relatively uniform, indicating that the growth of the coating structure is relatively good.

[0094] Figure 5 (Y prepared in Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating cross section SEM and EDS comparison. It can be seen that the cross-sectional morphology of the coating is a feather-shaped columnar high strain tolerance structure: the bottom coating is composed of columnar primary crystals and dendrites with a large porosity; the top is composed of a loose columnar crystal sequence, and many ungrown secondary dendrites form the "cauliflower head" area. The distribution of elements on the coating cross section is relatively uniform, and there is no obvious element segregation phenomenon, which proves that the (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating.

[0095] Figure 6 (Y prepared in Example 2 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 pre-sintered powder before and after high temperature heat treatment at 1600℃ for 10h. It can be seen that after high temperature heat treatment (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 pre-sintered powder diffraction peak intensity increases, the peak position shifts to a lower angle and is accompanied by a diffraction peak broadening phenomenon, but the phase composition does not change.

[0096] Comparative Example 1

[0097] Figure 7 This is the XRD comparison diagram of commercially available YSZ powder before and after high-temperature heat treatment at 1600℃ for 10h. It can be seen that before high-temperature heat treatment, the YSZ powder is mainly t-phase, with a small amount of m-phase. During the heat treatment, a transformation from t-phase to m-phase and c-phase occurred. After heat treatment, the YSZ powder is mainly c-phase, with a certain amount of m-phase and a small amount of t-phase. Since the phase change of YSZ is often accompanied by volume contraction or expansion, especially during thermal cycling, this volume change will continue to accumulate and generate thermal stress. When the stress accumulates to a certain extent, the coating will peel off and fail. And (Y0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 did not undergo phase change after high temperature heat treatment. 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 has excellent high temperature phase stability at 1600℃.

[0098] Comparative Example 2

[0099] The chemical formula of the coating is Gd2Zr2O7, and the preparation method is the same as that in Example 2.

[0100] The coatings obtained in Example 2 and Comparative Example 2 were tested for mechanical properties by nanoindentation, and the test results are as follows:

[0101] Table 1 Mechanical properties test results of coatings in Example 2 and Comparative Example 2

[0102] Elastic modulus(GPa) Hardness(GPa) Example 2 104.83 6.06 Comparative Example 2 134.84 7.58

[0103] The above results show that (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 The elastic modulus (104.83 GPa) of the 2Zr2O7 high entropy ceramic thermal barrier coating is much lower than that of the Gd2Zr2O7 coating (134.84 GPa), and the hardness is also lower than that of the Gd2Zr2O7 coating. The lower elastic modulus can improve the stress-strain tolerance of the ceramic layer and avoid coating failure caused by stress concentration. Therefore, (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7 high entropy ceramic thermal barrier coating has good mechanical properties.

[0104] In summary, the present invention successfully prepared (Y) by PS-PVD technology for the first time. 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2)2Zr2O7 high entropy ceramic thermal barrier coating, proving that it has high fracture toughness. Compared with the prior art, the high entropy ceramic thermal barrier coating of the present invention not only has excellent high temperature phase stability, but also has good mechanical properties. The high entropy ceramic thermal barrier coating of the present invention and its preparation method provide a way of thinking for the preparation of high entropy ceramic coatings of other systems, and have very broad application prospects in the field of thermal barrier coating materials for aircraft engines and gas turbines.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high entropy ceramic thermal barrier coating, It is characterized in that The chemical formula of the high entropy ceramic thermal barrier coating is (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) 2 Zr 2 O, wherein the percentage of the molar number of each rare earth element to the total molar number of all rare earth elements is 18% to 22% respectively, and the high entropy ceramic thermal barrier coating has a fluorite phase structure, and the cross-sectional morphology is a feather-type columnar high strain tolerance structure; the bottom coating is composed of columnar main crystals and dendrites, and the top is composed of a loose columnar crystal sequence.

2. The high entropy ceramic thermal barrier coating according to claim 1, It is characterized in that The thickness of the high entropy ceramic thermal barrier coating is 350-400 μm.

3. The method for preparing the high entropy ceramic thermal barrier coating according to claim 1 or 2, It is characterized in that include: The raw materials were weighed and wet-milled and dried, and the obtained mixed powder was crushed and granulated after pre-sintering to obtain (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) 2 Zr 2 O agglomerated powder, and then the (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) 2 Zr 2 O agglomerated powder is deposited on the surface of the substrate to form (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) 2 Zr 2 O High entropy ceramic thermal barrier coatings.

4. The method for preparing a high entropy ceramic thermal barrier coating according to claim 3, It is characterized in that The raw material includes ZrO 2 and rare earth oxide powder, the rare earth oxide comprising Y 2 O 3 、Sm 2 O 3 、Eu 2 O 3 , Gd 2 O 3 and Yb 2 O 3 .

5. The method for preparing a high entropy ceramic thermal barrier coating according to claim 4, It is characterized in that The ZrO 2 The particle size is 0.2-1μm and the mass purity is ≥99.99%.

6. The method for preparing a high entropy ceramic thermal barrier coating according to claim 5, It is characterized in that The particle size of the rare earth oxide is 5-10 μm, and the mass purity is ≥99.99%.

7. The method for preparing a high entropy ceramic thermal barrier coating according to claim 3, It is characterized in that The ball milling medium of the wet ball milling is ethanol, and the ball milling beads are made of ZrO 2 , the rotation speed is 300-400rpm, and the ball milling mixing time is 8-24h.

8. The method for preparing a high entropy ceramic thermal barrier coating according to claim 3, It is characterized in that The drying temperature of the drying is 105-120° C., and the drying time is 10-12 hours.

9. The method for preparing a high entropy ceramic thermal barrier coating according to claim 3, It is characterized in that The pre-sintering temperature is 1500-1600° C., and the pre-sintering time is 2-10 hours.

10. The method for preparing a high entropy ceramic thermal barrier coating according to claim 3, It is characterized in that The spray drying parameters in the secondary granulation process are: solid content 40-65%, dispersant 6-10% PAA, binder 8-10% PVP, inlet temperature 240-260°C, outlet temperature 110-130°C, feed speed 30-50rpm, spray speed 5-6m3 / h, and air pressure 2-3bar.

11. The method for preparing a high entropy ceramic thermal barrier coating according to claim 3, It is characterized in that The (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 ) 2 Zr 2 When the agglomerated powder is deposited on the surface of the substrate, the spraying parameters are: spraying distance 800-1000mm, spray gun moving speed 300-500mm / s, temperature 900-1000℃, powder feeding rate 5-10g / min, carrier gas flow rate 5-20SLPM, argon flow rate 25-40SLPM helium flow rate 40-60SLPM, oxygen flow rate 0-5SLPM, current 2400-2700A, and cabin pressure 4-6×10-5MPa.

12. Use of the high entropy ceramic thermal barrier coating as claimed in claim 1 or 2 in aircraft engines and gas turbines.

Citation Information

Patent Citations

  • High-entropy ceramic powder used for thermal barrier coating and preparation method of ceramic powder

    CN110272278A

  • High-entropy oxide ultra-high-temperature thermal barrier coating prepared through EB-PVD technology and method thereof

    CN114000107A

  • Low-thermal-conductivity high-entropy ceramic thermal barrier coating material

    CN114149260A

  • CMAS-corrosion-resistant high-entropy ceramic material with small grain size and preparation method of CMAS-corrosion-resistant high-entropy ceramic material

    CN114671675A

  • Thermal barrier coating as well as preparation method and application thereof

    CN115011905A